Peran Keluarga dalam Meningkatkan Motivasi Belajar Siswa di Era Pandemi Covid-19 - Julaeha, Engkam; Tafsir, Ahmad; Helmawati, Helmawati (Magister Pendidikan Agama Islam Universitas Islam Nusantara, 2022)
This research is motivated by the phenomenon that occurs in today's society, namely the role of parents is needed in the distance learning process. Parents as motivators in providing motivation, attention and also support for children during learning activities. The specific purpose of the researcher is to find out the role of the family (parents) as a motivator in increasing students' learning motivation in the era of the Covid-19 pandemic. And to find out the various obstacles and solutions faced by the role of the family as a motivator in increasing student learning motivation in the Covid-19 pandemic era. This researcher uses a qualitative method with descriptive analysis. Data collection techniques were carried out through observation, interviews, and documentation studies. The results of the research on the role of families in increasing students' learning motivation during the Covid-19 pandemic show that parents have high enthusiasm in teaching their children at home, especially mothers who accompany their children more all the time. There are parents who pay less attention to their children's learning because they have very busy jobs so that children learn on their own, but there are also parents who are very concerned about their children's school assignments and guide and direct them. The obstacles and solutions in this research are factors that constrain the occurrence of the online learning process carried out by students / students, including: lack of time given by parents, lack of parental knowledge about children's learning, lack of facilities and infrastructure provided by parents, On the other hand there are solutions to support the occurrence of online learning, but only apply to parents who are able and have a lot of time as follows: 1) educators, namely nurturing, educating, fostering and training children so that they achieve developmental tasks appropriately and optimally, 2) people parents as motivators, in this case parents must always provide encouragement to their children to have a passion for learning, especially studying at home as a support for successful achievement in school. 3) facilitator, parents must provide facilities, fulfill family/child needs in the form of clothing, food and shelter, including speed oh education. and 4). Parents as mentors, the role of parents is to accompany, and guide their children in learning and provide assistance to children when experiencing learning difficulties. Constraints and solutions are used as motivation to make learning at home more optimal